Standard operating procedure for the management of hypertensive urgencies in a community health centre in rural Tamil Nadu: a quality improvement project - Menezes, Anna Rachel (International Journal Of Community Medicine And Public Health, 2022)
Background: Hypertension is one of the heaviest health care burdens in rural India where less than 1/10th of patients has blood pressures under control. This sheds limelight on community healthcare centers to proactively prevent, manage and treat hypertension and its complications. St. Ann’s Hospital is one such CHC located in the Elathigiri subdisrtict of Tamil Nadu. We formulated a standard operating procedure at the CHC for the effective prevention and treatment of hypertensive urgency- one of the easily treatable but highly impactful complications of hypertension. We then strengthened its usage using plan-do-study-act cycles Methods: An SOP was formulated using international and national guidelines, contoured to the low resources present at the center. Healthcare workers were trained to follow the SOP. Sequential PDSA cycles were then used to evaluate and control the step-ladder of barriers in effective management. The results were analyzed using indicators and compared to baseline values established at the start of the study. Results: A rise of 41.4% was seen in correct SOP execution at the end of PDSA-2. At the end of the study, there was a 22% increase in the percent of patients correctly diagnosed, 19% increase in patients stabilized in the first hour and 14% increase in patients returning for follow up visits (p<0.05). Conclusions: Our SOP could significantly reduce the burden of HU at the CHC. We encourage its usage in similar low resource centers and promote PDSA cycles as a method to ensure its efficient utilization.